The road home - Harrison, Jim (Atlantic Monthly Press, 1998)
A man who was offered for adoption at birth because he was an illegitimate child searches for his mother in this novel on a Nebraska family. In the process, Nelse Carlson, 30, discovers he is the grandson of a powerful rancher.
Keywords: Families -- Nebraska -- Fiction; Indians -- Mixed descent -- Fiction; Nature stories; Nebraska -- Fiction; Historical fiction